The Effect of Profitability, Leverage, Liquidity, and the Company Size on Aggressiveness Tax the Sector Companies Consumer Goods Industry That Listed On The Indonesia Stock Exchange Year 2014-2016 - Riana Rachmawati Dewi, Erna Setyowati, Kartika Hendra Titisari & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This research aims to examine and analyze the effect of profitability,leverage, liquidity, and company size on the tax aggressivenes. The taxaggressivenes is an independent variablethat is measure by the ETR(Effective Tax Rate). Variable dependent is an profitability, leverage,liquidity, and company size. The population in this study is sectorcompanies consumer goods industry that listed on The Indonesia StockExchange in period 2014-2016. Sampling technique using purposivesampling method obtained by samples of 62 sector companies consumergoods industry that listed on The Indonesia Stock Exchange in period 2014-2016. Data used in this study is secondary data. This research used data inthe form of corporate financial statements contained in The Indonesia StockExchange (IDX) and www.idx.co.id website. Data analysis method used ismultiple linear regression. The result shows that the profitability, leverage,dan size of company do not affect impact on tax aggressiveness. Meanwhile,liquidity affect impact on tax aggressiveness. Based on the determinationcoefficient test (R2) obtained the coefficient of determination with adjustedR2 of 0,093. This result show that 9,3% of variables tax aggressivenes canbe explained by the profitability, leverage, liquidity, and company size.While, the rest of 91,7% is explained by other factors outside in thisresearch.Keywords: Aggressiveness Tax, Profitability, Leverage, Liquidity, and Company Size.